„Pro salute anime…” – zapisy pobożne w testamentach mieszczan płockich w świetle księgi ławniczej Płocka 1489 – 1517 - Offerczak, Bartłomiej (Saeculum Christianum. Pismo Historyczne, 2019)
The aim of this article was to show the attitudes of Plock townspeople towards death through their wills, which were included in the pages of the Plock jury book between 1489-1517. The article presents individual Plock townspeople who left legacies for churches, city fraternities or the poor in their testaments. At the end of the article, tables summarize all the testamentary legacies for the benefit of the mentioned municipal institutions of late medieval Plock.